Prognosing Economic Processes and Economic Planning of the Market Economy - Dievulis, Gediminas (Ekonomika, 1997)
The possibilities of planning the market economy by using the indicative planning principles are discussed as well as the experience acquired from the planned economics and developing formal planning models. We also suggest using formal methods for the prediction of economic processes when the necessary conditions are created. It is stated that the planned transition from the centrally planned economy to the market economy could have diminished social and economic losses within the transitional period.